Digitizing Grocery Retailing: The Role of Emerging Technologies in the Value Chain - Weyer, Julia; Tiberius, Victor; Bican, Peter; Kraus, Sascha (International Journal of Innovation and Technology Management, 2021)
Multiple emerging technologies both threaten grocers and offer them attractive opportunities to enhance their value propositions, improve processes, reduce costs, and therefore generate competitive advantages. Among the variety of technological innovations and considering the scarcity of resources, it is unclear which technologies to focus on and where to implement them in the value chain. To develop the most probable technology forecast that addresses the application of emerging technologies in the grocery value chain within the current decade, we conduct a two-stage Delphi study. Our results suggest a high relevance of almost all technologies. The panel is only skeptical about three specific projections. As a consequence, grocers are advised to build up knowledge regarding the application of these technologies in the most promising areas of their value chain. © 2020 World Scientific Publishing Company.
CRIS-Team Scopus Importer:2021-05-14
Keywords: artificial intelligence; augmented reality; big data analytics; blockchain technology; Delphi study; drones; grocery retailing; RFID; technological forecasting